Struktura czasu pracy i wydajność maszyn podczas rozdrabniania karp - Gałęzia, Tomasz (Leśne Prace Badawcze, 2017)
This study was carried out at a roadside landing of the Augustów Forest District in order to determine the structure of a typical working day for machines involved in stump crushing as well as the overall efficiency of the process and the machinery’s fuel consumption. The machines involved in the entire process were a front-loader, a shredder, a screen and a truck-tractor unit. Machinery activity was recorded using a sampling method with a three-minute interval. During 16 hours of observation, 533 stumps were crushed to produce 362 m 3 lv of timber particles in total and the average operational productivity reached 28 m 3 lv h -1 . Based on the amount of consumed fuel and its energy content, the energy input of the process was calculated to be 103.33 MJ m -3 lv which is 3640.53 MJ m -3 lv less than the output of energy gained at the power plant. Total CO 2 emissions of the processing machinery and transport off the forest site were estimated using previously published data and amounted to 7.58 kg m -3 lv.